Salivary miRNA 18a-5p Expression Level in Oral Squamous Cell Carcinoma - Mukesh Kumar, Fouzia Shaikh, Santosh Kumar, Shumaila Usman, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the expression level of the salivary microRNA 18a-5p in Oral squamous cell carcinoma patients and healthy individuals Methodology: This case-control study was conducted on 40 samples out of which 20 were OSCC patients and 20 were healthy control patients. Saliva was collected from patients with newly diagnosed OSCC and healthy controls after getting informed written consent. All samples were recruited from Abbasi Shaheed hospital and Ziauddin University Hospital, Karachi. We evaluated the miRNA 18a-5p expression level in the saliva by reverse transcriptase polymerase chain reaction (RT-PCR) after isolating RNA through TRIZOL method. Results: microRNA 18a-5p expression level was significantly expressed and higher in OSCC samples compared with controls moreover in the OSCC samples with the progression of stages and grades, the expression increased suggesting it tumor-promoting role in OSCC. Conclusion: Our study concludes that the microRNA18a-5p can be the potential non-invasive biomarker for early detection of OSCC. Keywords: Oral squamous cell carcinoma, microRNA, salivary biomarker